2013
DOI: 10.1111/joor.12118
|View full text |Cite
|
Sign up to set email alerts
|

Salivary cortisol and psychological factors in women with chronic and acute oro‐facial pain

Abstract: The aim of this study was to compare the salivary cortisol level, pain intensity and psychological factors between patients with chronic and acute oro-facial pain (OP) and pain-free subjects. Twenty-seven females with chronic OP (a diagnosis of myofascial pain according to the Research Diagnostic Criteria for Temporomandibular Disorders with at least 6 months duration), 24 females with acute OP (<10 days duration) and 27 pain-free females participated. Morning saliva was collected from all participants for ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 43 publications
1
23
0
4
Order By: Relevance
“…Jasim et al [32] reported that patients with chronic MFP show significantly higher scores of depression symptoms, somatization and perceived stress compared to patients with acute pain. In the current study, the differences in anxiety and depression levels were considered clinically significant rather than just statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Jasim et al [32] reported that patients with chronic MFP show significantly higher scores of depression symptoms, somatization and perceived stress compared to patients with acute pain. In the current study, the differences in anxiety and depression levels were considered clinically significant rather than just statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…A presença de DTM dolorosa leva a maior predisposição à ansiedade (REISSMANN et al, 2014) e indivíduos mais ansiosos são mais susceptíveis a perceberem dor nos quadros clínicos de DTM (DIRAÇOǦLU et al, 2016 (LAMBERT et al, 2013;JASIM et al, 2014;JO et al, 2016), em oposição a outros estudos que demostraram que esta diferença existe (SALAMEH et al, 2015;LIN et al, 2016). No presente estudo não foi verificada diferença nas dosagens do cortisol salivar de mulheres com DTM dolorosa em comparação à mulheres controles, bem como ao longo da LLLT.…”
Section: Sensibilidade à Dor (Limiar De Dor à Pressão)unclassified
“…Na dor crônica os eventos estressores são persistentes, de menor intensidade e variam de acordo com as características individuais de cada paciente. Portanto, é relevante considerar que haja habituação aos estímulos estressores na dor crônica, não ocasionando grandes flutuações no cortisol em comparação à indivíduos sem dor (LAMBERT et al, 2013;JASIM et al, 2014, JO et al, 2016.…”
Section: Sensibilidade à Dor (Limiar De Dor à Pressão)unclassified
See 2 more Smart Citations